Modelling of Magma Density and Viscocity Changes and Their Influences towards the Characteristic of Kelud Volcano Eruption - Humaida, Hanik; Brotopuspito, K. S.; Pranowo, H. D.; narsito, narsito (Indonesian Journal on Geoscience, 2011)
DOI: 10.17014/ijog.v6i4.129The effusive eruption of Kelud Volcano in 2007 was different from the previous ones, which in general were more explosive. Among others, density and viscosity are factors that determine the type of eruption. Therefore, the study on the difference of the recent eruption style based on the density and viscosity of magma was carried out. The method used in this study was based on geochemical analysis of the rock and then a modeling was established by using the above parameter. The study on the explosive eruption was emphasized on the data of 1990 eruption, whereas the effusive eruption was based on the data of 2007 eruption. The result shows that the magma viscosity of Kelud Volcano depend on the H O concentration as one of the volatile compound in magma, and temperature which gives the exponential equation. The higher the increase of H O content the smaller the value of its viscosity as well as the higher the temperature. The H O content in silica fluid can break the polymer bond of the silica fluid, because a shorter polymer will produce a lower viscosity. The density of the silica content of Kelud Volcano ranges between andesitic and basaltic types, but andesite is more likely. The fluid density of the material of 1990 eruption is different from 2007 eruption. Compared to the 2007, the 1990 eruption material gave a lower density value in its silica fluid than that of the 2007 one. The low density value of the silica fluid of the 1990 eruption material was reflecting a more acid magma. The level of density value of silica fluid depends on its temperature. At the temperature of 1073 K the density of the 1990 Kelud magma is 2810 kg/m3 and the 2007 magma is 2818 kg/m3, whereas at a temperature of 1673 K, the density is 2672 kg/m3 and 2682 kg/m3 of the 1990 and 2007 eruptions respectively. A modeling by using an ideal gas law of Henry’s Law illustrated that the ascent of Kelud’s magma to the surface may cause changes in it’s physical properties. The evolution of the flow pressure in the conduit is characterized by three different areas; based of the conduit until the pressure is saturated, then at the level between release and fragmentation, and then the level above the fragmentation, that implicates the decrease in the wall friction.